Comparison of Induction of Labor versus Expectant Management in Reducing Maternal Infections in PROM Patients in Tishreen University Hospital in Lattakia 2018-2019 - ديوب, ميسون; حسن, لؤي; داؤد, دينا (Latakia University Journal -Medical Sciences Series, 2020)
Background and objective: The greater the time between membranes rupture and childbirth, the greater the risk of infection. It is unknown whether induction of labor will cause a decrease in the incidence of infectious complications or if it will cause an increase in cesarean sections rate. Patients and methods: We studied 100 patients with term PROM. Half of them were managed by expectant protocol, up to 12 hours and the other half by induction of labor directly was upon admission. Main studied outcomes were maternal infections and need for cesarean section. Results: the rates of Caesarean section were significantly higher in the induction group 32% versus 10%. Clinical Chorioamnionitis was less likely to happen in induction group, but Endometritis was less likely to happen in expectant management group. However, these two differences of complications were not statistically significant. Conclusion: Expectant management in cases of term PROM reduces the need for a cesarean section with no increase in maternal infections.